Primerjava testov UNB in ACMC pri otrocih po amputaciji zgornjega uda - uvodni rezultati - Brezovar, Darinka (Rehabilitacija (Ljubljana), 2012)
Background: The aim of the study was to find out whether UNB and ACMC are measuring the same construct. Methods: All children and adolescent visiting the upper limb prosthetic clinic in Ljubljana in 2009 were included into the study. They were all assessed by age-appropriate UNB subtest and ACMC test. Results: Nine boys and seven girls aged two to 21 years (13 year on average) were included into study. Twelve had myoelectric and four had body-powered prosthesis. High positive correlation between UNB skill and ACMC was observed (r = 0.777, p < 0.001), and medium positive correlation between UNB spontaneity and ACMC (r = 0.577, p = 0.006). Conclusions: For the children and adolescents included into the study, the tests are comparable and measure the same construct.
Keywords: amputacija; Amputation; izid, ocenjevanje (zdravstveno varstvo); Outcome assessment (health care); rehabilitacija; Rehabilitation; Upper extremity; vocational rehabilitation; zgornja ekstremiteta; zgornji ud